ANALYSIS OF GRANDPARENTING PATTERNS IN CHILDREN'S CHARACTER FORMATION IN LAMONGAN CITY - Nafisah, Aisyah Durrotun; Nabelah, Shinta; Zahrok, Fatimatuz; Arlika, Fivin Aulia; Rohmatina, Zuhriya Lutfi; Ningtyas, Anesti Wahyu; Rahayu, Novita Christy (UIN Fatmawati Sukarno Bengkulu, 2024)
Grandparenting is child care carried out by grandparents for certain reasons. Child care should be the responsibility of both parents, but due to several factors the child's care has been transferred to his grandparents. Grandparenting parenting can shape a child's character. The method in this research uses descriptive qualitative research. The results of the research show that the parenting style used by grandparents in forming children's character in Lamongan applies 3 children's character formation, namely religious character, independent character and disciplinary character. The impact of grandparenting parenting on children's character development is that children tend to be more spoiled, very difficult to tell, stubborn, and all their grandchildren's requests are always granted. It can be concluded that a small percentage of the subjects of this research have a character that tends to be spoiled, in the sense that their every wish must be fulfilled by the grandparents.